THE EFFECTS OF SOCIETAL FACTORS ON RELIGIOUS TOLERANCE IN STUDENTS OF THE PHILOSOPHICAL FACULTIES IN SKOPJE AND TETOVO (R.NORTH MACEDONIA) - Dushka Matevska; Zoran Matevski (Center for Study of Religion and Religious Tolerance University of Belgrade, 2021)
This paper has the goal of finding out whether there is a causal link between, and if yes, the degree of influence of the socio-economic status, family type, ethnicity, gender, and confessional belonging on religious tolerance in students of the Philosophical Faculties in Skopje and Tetovo. In accordance with the subject of this paper, the basic goal of this paper is to pinpoint the societal factors that affect religious tolerance in the student population. This research has the following goals: to pinpoint the most influential societal factors that influence religious tolerance in the students of the Philosophical Faculties in Skopje and Tetovo; to underline religious tolerance as a socially desirable behavior in the student population in the midst of the multiconfessional and multiethnic reality of the country; whether or not, and if so in what way, does the Macedonian Orthodox Church - Archbishopric of Ohrid and the Islamic Faith Community are promoters of religious tolerance in the student population; to pinpoint the confessional characteristics of religious tolerance in the student population (the characteristics of Christian and Muslim tolerance). From a methodological point of view, this research is geared towards estimation of the influence of societal factors (socioeconomic status, family type, ethnicity, gender, and the kind of confessional belonging) over classical religious tolerance in the students of Skopje and Tetovo. This paper will try to find the causal links between these factors and religious tolerance in students. The research method is combined i.e. the paper consists of both a qualitative and a quantitative approach.
Keywords: tolerance; students; societal factors; muticonfessional reality